2008
DOI: 10.1073/pnas.0806494105
|View full text |Cite
|
Sign up to set email alerts
|

Electron injection into organic semiconductor devices from high work function cathodes

Abstract: We show that polymer light-emitting diodes with high workfunction cathodes and conjugated polyelectrolyte injection/transport layers exhibit excellent efficiencies despite large electroninjection barriers. Correlation of device response times with structure provides evidence that the electron-injection mechanism involves redistribution of the ions within the polyelectrolyte electron-transport layer and hole accumulation at the interface between the emissive and electron-transport layers. Both processes lead to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
145
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 132 publications
(150 citation statements)
references
References 52 publications
5
145
0
Order By: Relevance
“…16,17 This situation is similar to the behaviour observed for PLEDs with deep charge traps. 18 In an attempt to address such issues, Fang et al fabricated PLEDs with zwitterionic CPEs in which both anions and cations are covalently attached to the polymer side chains; 19 the resulting PLED transient response was then ~1-100 μs.…”
Section: Introductionsupporting
confidence: 82%
“…16,17 This situation is similar to the behaviour observed for PLEDs with deep charge traps. 18 In an attempt to address such issues, Fang et al fabricated PLEDs with zwitterionic CPEs in which both anions and cations are covalently attached to the polymer side chains; 19 the resulting PLED transient response was then ~1-100 μs.…”
Section: Introductionsupporting
confidence: 82%
“…[ 1,5,6 ] A recent study on conjugated polymer zwitterions revealed a similar lowering in work function, attributed to electrostatic realignment of the dipolar zwitterionic side-chains near the metal interface. [ 18 ] The formation of interfacial dipoles and electric fi eld-induced reorientation of molecules has also been reported.…”
Section: Introductionmentioning
confidence: 97%
“…[ 20 ] The relatively low ionic mobility can result in slow transient behavior during device operation. [ 5 ] Modifi cation of the work function can also occur due to dipole formation induced by integer or partial charge transfer between the substrate and the WML (Figure 5 b). Charge transfer can take place in a large variety of circumstances as reviewed by Braun et al in Ref.…”
Section: Considered Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…[6][7][8][9][10][11][12] A range of CPEs with different counterions (anion/cation) and backbones 13,14 have been synthesized in attempts to understand the role of the ions in the charge injection process. 15,16 The promising electronic properties of CPEs in combination with their solubility in polar solvents offer a unique route to the realization of high-performance polymer light-emitting diodes (PLEDs) without the use of reactive Ca or Ba cathodes.…”
mentioning
confidence: 99%